Effect of salt and smoke on quality and shelf life of salt-smoke-dried batashi (Neotropius atherinoides) kept at different storage condition (Research in Agriculture Livestock and Fisheries, 2016)
This study was carried out to assess the changes in microbiological and biochemical aspects of fresh, smoked, salt-smoke-dried (SSD), control dried (CD; treated without salt and smoke) batashi (Neotropius atherinoides) during storage at ambient temperature (26-28oC) and refrigeration temperature (4oC). The main objective of this study was to investigate the effect of natural preservatives such as salt and smoke on the shelf life of the product over the storage period. The moisture content of fresh batashi was 75.81% whereas 18.10% for SSD batashi. The initial value of protein, fat and ash content of SSD batashi was 65.93, 17.09 and 16.90% on dry matter basis. During storage period (60 days), the percentage of moisture increased whereas protein, fat, and ash content considerably decreased. After two month storage at ambient temperature the protein, lipid and ash content for SSD batashi were 65.0, 15.9 and 15.95%, respectively whereas the values of the same parameters stored at refrigeration temperature were 65.03, 16.16 and 16.12%, respectively on dry matter basis. The initial TVB-N and SPC value for SSD batashi was 6.10mg/100g and 1.14×104 CFU/g respectively. During storage period TVB-N and SPC value slowly increased and the values reached to 17.94 mg/100g and 4.2×104 CFU/g, respectively for salt-smokedried batashi, stored at ambient condition whereas 11.20 mg/100g and 2.42×104 CFU/g, respectively for the products stored at refrigeration temperature. Because of using salt and smoke as natural preservatives, no yeast or mould was detected in salt-smoke-dried batashi fish. Therefore, it can be inferred that salt and smoke treated dried fish products has longer shelf life than plain dried product (without treated with salt and smoke). From the overall performance, the products kept at refrigeration temperature showed better shelf life than the products stored at ambient temperature.Res. Agric., Livest. Fish.3(3): 443-451, December 2016